Mobile payment security governance framework for mobile network operators in Zimbabwe - Mugwagwa, Tauya (Midlands State University, 2017)
“Technological process is like an axe in the hands of a pathological criminal.” (Einstein 2015).The non-existent mobile payment security governance framework for Mobile Network Operators (MNOs) is directly or otherwise, causing constant challenges to mobile payment systems (MPS) subscribers who include systems and service providers, and operators and general clients in Zimbabwe. Consequently, there is perceived yet undetermined lack of clientele trust, confidence and convenience among MPS subscribers; suspected lack of accountability, transparency, fairness and good governance resulting from insufficient legal, policy and regulatory guidelines. However, there is no sufficient metric to measure the quality of security governance in institutions. Emerging frontiers that advance MPS clientelism ensue. For the purpose of this study, the regulator for MPS governance is limited but not restricted to the Postal Telecommunications Regulatory Authority of Zimbabwe (POTRAZ). The target operators include NetOne, Telecel and Econet. The target MPS providers include banks. The study population includes but is not exclusive of the banked and unbanked MPS clients. Anecdotal evidence indicates that counterfeits of the MPS governance framework for MNOs in Zimbabwe are affecting the corporate images of banks and clients in many ways. Clients are the key investors; inversely they are the most affected. The non-existent MPS governance framework is suspected to be undermining the very fabric of MPS actual systems use which includes its computability, compatibility, acceptability, applicability, reliability and viability. These counterfeits fundamentally buttress clientele trust, confidence and convenience. As trust shrinks, so raises the claim for clientelism. By and large, the capacity and autonomy of the MPS governance framework for MNOs in Zimbabwe are put on the radar, and interrogated in the clientele domain. In order to mitigate the indifference of the MPS governance framework on customers, a grounded client centric model is proposed for implementation. This study interrogates the legal, policy, regulatory and technological challenges created by the MPS governance framework for MNOs in Zimbabwe. The purpose of the study is to develop and enhance the beneficial participation of clients in MPS governance. The option to cross examine MNOs is informed by the view that MPS actual cyber and social systems transactions evolve around MNOs. Subsequently, this study tests the hypothesis that an enabling and proficient control MPS governance framework for MNOs influences MPS best practice which is intrinsically connected with or incidental to the customers’ perceived demand for clientele trust, confidence and conveniences in MPS actual cyber and social systems use. In order to effectively interrogate the capacity and autonomy of the MPS legal, policy, regulatory and technological terrain, show cause and facilitate the development and enhancement of clients’ full participation; this study sources grounded qualitative data from MPS clients, operators, service providers and the regulator. The grounded case oriented perspective presents compelling grounded qualitative data for academic and expert reviews. Resulting from the academic and expert reviews, an enabling and proficient control MPS governance framework for MNOs in Zimbabwe is proposed. Conclusions, recommendations and areas for further research are submitted for future considerations.